2021
DOI: 10.1002/chem.202100608
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Kinetic Factors of ortho‐Benzyne Formation in Hexadehydro‐Diels‐Alder (HDDA) Reactions

Abstract: With the rapid development of the hexadehydro-Diels-Alder reaction (HDDA) from its first discovery in 1997, the question of whether a concerted or stepwise mechanism better describes the thermally activated formation of orthobenzyne from a diyne and a diynophile has been debated. Mechanistic and kinetic investigations were able to show that this is not a black or white situation, as minor changes can tip the balance. For that reason, especially, linked yne-diynes were studied to examine steric, electronic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…), and their varieties are diverse (Scheme 1b). 9,10 In 1902, Stoermer and Kahlert et al reported the existence of the benzene species by treating 3-bromobenzofuran with a strong base in ethanol solution, 11 the usual strategy for the preparation of benzyne intermediates is to remove two adjacent atoms or groups from the benzene ring. Due to the instability, benzyne intermediate must be generated in situ from appropriate precursors under suitable reaction conditions, including thermo-synthesis, oxidation, deprotonation, halogen-metal exchange, C-Si bond cleavage by uoride source or decarboxylation by transition metal-catalyzed (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…), and their varieties are diverse (Scheme 1b). 9,10 In 1902, Stoermer and Kahlert et al reported the existence of the benzene species by treating 3-bromobenzofuran with a strong base in ethanol solution, 11 the usual strategy for the preparation of benzyne intermediates is to remove two adjacent atoms or groups from the benzene ring. Due to the instability, benzyne intermediate must be generated in situ from appropriate precursors under suitable reaction conditions, including thermo-synthesis, oxidation, deprotonation, halogen-metal exchange, C-Si bond cleavage by uoride source or decarboxylation by transition metal-catalyzed (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, didehydrogenated benzene biradicals (see Scheme 1) participate in important reactions such as the Bergman cyclization in which a 1,4‐didehydrobenzyne ( p ‐benzyne) biradical is involved 5–29 . Additionally, the more stable o ‐benzyne isomer also participates as an intermediate in various organic reactions, such as Diels–Alder, the formation of epoxides, and the synthesis of various organic compounds 4,30–39 …”
Section: Introductionmentioning
confidence: 99%